Analisis Efektivitas Pemadatan Tanah Berdasarkan Uji Laboratorium dan Lapangan pada Pekerjaan Timbunan Tanah di Sulawesi Tenggara - Minmahddun, Anafi (Unmuh Babel Press, 2025)
Soil compaction is a critical phase in construction projects, particularly those requiring long-term structural stability. The compaction process aims to increase soil density, enabling the soil to support structural loads without excessive settlement. This study was conducted to evaluate the effectiveness of soil compaction used as fill material in an industrial development project in Southeast Sulawesi. A quantitative approach was employed by combining laboratory testing using the standard Proctor method and field evaluation using the sand cone method. Soil samples were directly taken from the project site and tested in the laboratory to determine the maximum dry density (γdmax) and the optimum moisture content (wopt). Laboratory results indicated a γdmax of 1.69 gr/cm³ and a wopt of 28.80%. Subsequently, sand cone tests were performed at eight field locations after the compaction process was completed. The results showed that the field degree of compaction ranged from 77.8% to 90.4%, which is below the minimum technical standard of 95%. This discrepancy is attributed to excessive moisture content and a lack of control in field execution. The study highlights the importance of synchronizing laboratory data with field implementation. The findings provide valuable recommendations on moisture control, appropriate equipment selection, and operator training to improve soil compaction quality in future construction projects.